Effectiveness of simulation-based learning in Malaysian higher education: A case study of MonsoonSIM - Aisyah, Mohd Khalil; Lee, Khai Loon; Zetty Ain, Kamaruzzaman; Ong, Chin An (Emerald Group Publishing Ltd., 2024)
Purpose: Higher education institutions (HEIs) face the formidable responsibility of equipping students with the requisite knowledge and skills essential for a successful transition into the professional workforce. In contemporary education, simulation-based learning (SBL) has emerged as a pivotal tool employed by HEIs to facilitate and enhance the learning experience. MonsoonSIM stands out as a notable simulation-based experiential learning platform, encompassing a wide spectrum of business processes. This study aims to investigate the effectiveness of SBL in Malaysian HEI, with a specific focus on utilizing MonsoonSIM to bolster students' knowledge and skills. Design/methodology/approach: To gather empirical evidence, an online survey questionnaire was methodically distributed to 254 students enrolled in Malaysian HEIs, employing purposive sampling techniques. A total of 114 valid responses were collected and subjected to rigorous analysis using SmartPLS4, leveraging the partial least squares structural equation modeling methodology. Findings: The outcomes of this investigation shed light on the positive influence of marketing management knowledge on the effectiveness of SBL. However, it was observed that problem-solving and critical thinking skills, financial management and production management knowledge did not exhibit a statistically significant impact on the effectiveness of SBL. Originality/value: This study contributes to the existing body of knowledge by offering valuable insights into how students engage with and derive learning outcomes from simulation-based educational tools. The findings underscore the pivotal role of integrating SBL into the broader pedagogical framework to enhance the overall learning experience.